Thin film as well as preparation method and application thereof

By depositing a metal film layer with better conductivity on the substrate and depositing a titanium film layer thereon to form a multi-layer film structure, the problem of poor conductivity of the titanium film is solved, and the effect of effectively reducing resistance and improving conductivity is achieved.

CN119615092APending Publication Date: 2025-03-14FIRST RARE MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411812638.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, the titanium and titanium alloy films obtained by DC magnetron sputtering have relatively high resistivity and poor conductivity, and cannot be effectively improved by adjusting process parameters and heat treatment.

Method used

By depositing a copper, nickel or aluminum metal film layer with better conductivity on the substrate and depositing a titanium film layer thereon, a multi-layer film structure is formed to improve the overall conductivity.

Benefits of technology

This method effectively reduces the resistance of the titanium film and improves the conductivity of the film, while not affecting the performance of the titanium film.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of functional thin film materials, and discloses a thin film and a preparation method thereof.The thin film is composed of a metal thin film layer and a titanium thin film layer deposited on the metal thin film layer, and the metal thin film layer is selected from a copper thin film layer, a nickel thin film layer or an aluminum thin film layer; through matching of the metal film layer and the titanium film layer, the resistance of the titanium film layer can be effectively reduced, and the conductivity of the film is improved; in addition, the invention further discloses application of the thin film to preparation of foam iron, an LCD display or a thin film solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of functional thin film materials, and in particular to a thin film and a preparation method and application thereof. Background Art

[0002] In the current semiconductor device manufacturing fields such as photovoltaics and flat panel displays, magnetron sputtering thin film technology is widely used in the preparation of complex devices with specific functions. In order to meet the multiple needs of products, two or more layers of films with different materials and different functionalities are laminated and compounded through magnetron sputtering thin film technology in the actual process. Among them, the structure of metal and semiconductor laminated films is widely used.

[0003] Chinese patent application 202410717969.4 discloses a laminated film and a method for preparing the same, wherein the laminated film consists of a titanium film layer deposited on a substrate and an indium cerium titanium tantalum oxide film deposited on the titanium film layer, wherein the deposition method used is DC magnetron sputtering.

[0004] As we all know, the thin film layer formed by DC magnetron sputtering has a strong bonding force with the substrate, and the density and uniformity of the thin film layer are also relatively good. However, the resistivity of titanium and titanium alloy thin films obtained by DC magnetron sputtering is relatively high. Adjusting the sputtering process parameters such as power, working gas pressure, deposition temperature, and heat treating the thin film have failed to improve the poor conductivity of the titanium thin film. Therefore, improving the performance of titanium thin films has become a major problem that needs to be overcome.

[0005] The problem that this solution needs to solve is: how to reduce the resistance of titanium film and improve the conductivity of the film. Summary of the invention

[0006] The purpose of this application is to propose a film and its preparation method and application, which can effectively reduce the resistance of the titanium film and improve the conductivity of the film layer by combining a film formed by copper metal, nickel metal or aluminum metal with a titanium film.

[0007] To achieve the above object, the present application discloses a thin film, which is composed of a metal thin film layer and a titanium thin film layer deposited on the metal thin film layer;

[0008] And the metal film layer is a copper film layer, a nickel film layer or an aluminum film layer.

[0009] By using a copper thin film layer, a nickel thin film layer or an aluminum thin film layer in combination with a titanium thin film layer, a thin film with better conductivity is deposited on the substrate, which can generate more free electrons or holes, thereby increasing the overall carrier concentration of the thin film and improving the overall conductivity of the thin film without affecting the performance of the titanium thin film.

[0010] Preferably, the thickness of the film is 100 to 200 nm, and the thickness ratio of the metal film layer to the titanium film layer in the film is 1:1 to 1:3;

[0011] Further preferably, in some embodiments, the thickness of the film can be 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, or 200 nm.

[0012] Preferably, the metal film layer is obtained by DC magnetron sputtering of a metal target, wherein the metal target is a copper target, a nickel target or an aluminum target;

[0013] The titanium thin film layer is obtained by direct current magnetron sputtering of a titanium target.

[0014] Further preferably, the purity of the copper target, nickel target, aluminum target and titanium target is not less than 5N.

[0015] In addition, the preparation method of the above film is also disclosed:

[0016] Step 1: Cleaning the substrate;

[0017] Step 2: Mount the metal target material on the cathode position No. 1 target for DC magnetron sputtering to grow the metal film layer on the substrate to obtain the metal film layer on the substrate;

[0018] Step 3: Install the titanium target on the cathode position No. 2 target and perform DC magnetron sputtering to grow the titanium thin film layer on the metal thin film layer to obtain a thin film.

[0019] Preferably, the substrate is soda-lime glass or silicate glass having a mass fraction of calcium oxide not exceeding 12.5%;

[0020] The cleaning operation of the substrate is specifically as follows: cleaning and drying are performed in sequence by using acetone, anhydrous ethanol, and deionized water.

[0021] Preferably, the distance between the metal target and the center of the substrate in step 2 is 6 to 10 cm, and the target sputtering power density is 1.0 to 10.5 W / cm 2 , the target sputtering pressure is 0.2~0.6Pa, and the sputtering time is 40~200s;

[0022] The distance between the titanium target and the center of the substrate in step 3 is 6 to 10 cm, and the target sputtering power density is 1.0 to 5.2 W / cm 2 , the target sputtering pressure is 0.2~0.6Pa, and the sputtering time is 450~1200s.

[0023] In addition, the invention also discloses the use of the film for preparing foam iron, LCD display or thin film solar cell.

[0024] The beneficial effects of this application are:

[0025] The present application provides a thin film and its application. By depositing a copper thin film layer, a nickel thin film layer or an aluminum thin film layer with good conductivity on a substrate, more free electrons or holes can be generated, so that the overall carrier concentration of the thin film is increased, and the overall conductivity of the thin film is improved without affecting the performance of the titanium thin film. DETAILED DESCRIPTION

[0026] In the description of this application, it should be noted that if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0027] Example 1

[0028] A film is prepared by the following steps:

[0029] Step 1: Cleaning and drying the soda-lime glass with a mass fraction of calcium oxide of 10% with acetone, anhydrous ethanol and deionized water in sequence;

[0030] Step 2: installing a copper target material to the cathode target position 1, and then depositing a copper thin film layer on the soda-lime glass by DC magnetron sputtering in an argon atmosphere to obtain a copper thin film layer on the soda-lime glass, wherein the purity of the copper target material is 5N;

[0031] The distance between the copper target and the center of the soda-lime glass is 8 cm, and the target sputtering power density is 6 W / cm 2 , the target sputtering pressure is 0.4Pa, and the sputtering time is 65s;

[0032] Step 3: installing a titanium target material to the cathode target position 2, and then depositing a titanium thin film layer on the copper thin film layer by DC magnetron sputtering in an argon atmosphere to obtain a thin film on the soda-lime glass, wherein the purity of the titanium target material is 5N;

[0033] The distance between the titanium target and the center of the soda-lime glass is 8 cm, and the target sputtering power density is 3.1 W / cm 2 , the target sputtering pressure is 0.4Pa, and the sputtering time is 770s.

[0034] Wherein, in step 3, the total thickness of the film is 150 nm, and the thickness ratio of the copper film layer to the titanium film layer is 1:2.

[0035] Example 2

[0036] A film is prepared by the following steps:

[0037] Step 1: Cleaning and drying the soda-lime glass with a mass fraction of calcium oxide of 10% with acetone, anhydrous ethanol and deionized water in sequence;

[0038] Step 2: installing a copper target material to the cathode target position 1, and then depositing a copper thin film layer on the soda-lime glass by DC magnetron sputtering in an argon atmosphere to obtain a copper thin film layer on the soda-lime glass, wherein the purity of the copper target material is 5N;

[0039] The distance between the copper target and the center of the soda-lime glass is 6 cm, and the target sputtering power density is 1.0 W / cm 2 , the target sputtering pressure is 0.2Pa, and the sputtering time is 45s;

[0040] Step 3: installing a titanium target material to the cathode target position 2, and then depositing a titanium thin film layer on the copper thin film layer by DC magnetron sputtering in an argon atmosphere to obtain a thin film on the soda-lime glass, wherein the purity of the titanium target material is 5N;

[0041] The distance between the titanium target and the center of the soda-lime glass is 6 cm, and the target sputtering power density is 1.0 W / cm 2 , the target sputtering pressure is 0.2Pa, and the sputtering time is 495s.

[0042] Wherein, in step 3, the total thickness of the film is 100 nm, and the thickness ratio of the copper film layer to the titanium film layer is 1:2.

[0043] Example 3

[0044] A film is prepared by the following steps:

[0045] Step 1: Cleaning and drying the soda-lime glass with a mass fraction of calcium oxide of 10% with acetone, anhydrous ethanol and deionized water in sequence;

[0046] Step 2: installing a copper target material to the cathode target position 1, and then depositing a copper thin film layer on the soda-lime glass by DC magnetron sputtering in an argon atmosphere to obtain a copper thin film layer on the soda-lime glass, wherein the purity of the copper target material is 5N;

[0047] The distance between the copper target and the center of the soda-lime glass is 10 cm, and the target sputtering power density is 10.5 W / cm 2 , the target sputtering pressure is 0.6Pa, and the sputtering time is 165s;

[0048] Step 3: installing a titanium target material to the cathode target position 2, and then depositing a titanium thin film layer on the copper thin film layer by DC magnetron sputtering in an argon atmosphere to obtain a thin film on the soda-lime glass, wherein the purity of the titanium target material is 5N;

[0049] The distance between the titanium target and the center of the soda-lime glass is 10 cm, and the target sputtering power density is 5.2 W / cm2 , the target sputtering pressure is 0.6Pa, and the sputtering time is 1115s.

[0050] Wherein, in step 3, the total thickness of the film is 200 nm, and the thickness ratio of the copper film layer to the titanium film layer is 1:2.

[0051] Example 4

[0052] The method is basically the same as Example 1, except that the thickness ratio of the copper thin film layer to the titanium thin film layer is 1:1;

[0053] The sputtering time of the copper target is 95 s, and the sputtering time of the titanium target is 580 s.

[0054] Example 5

[0055] The method is basically the same as Example 1, except that the thickness ratio of the copper thin film layer to the titanium thin film layer is 1:3;

[0056] The sputtering time of the copper target is 50 s, and the sputtering time of the titanium target is 865 s.

[0057] Example 6

[0058] The method is basically the same as Example 1, except that in step 2, a nickel target material of the same purity is used to replace the copper target material for DC magnetron sputtering, and the sputtering time is 125 s to obtain a nickel thin film layer on the soda-lime glass;

[0059] The thickness ratio of the nickel thin film layer to the titanium thin film layer is 1:2.

[0060] Example 7

[0061] The method is basically the same as Example 1, except that in step 2, an aluminum target material of the same purity is used to replace the copper target material for DC magnetron sputtering, and the sputtering time is 80 seconds to obtain an aluminum thin film layer on the soda-lime glass;

[0062] The thickness ratio of the aluminum thin film layer to the titanium thin film layer is 1:2.

[0063] Comparative Example 1

[0064] A film is prepared by the following steps:

[0065] Step 1: Cleaning and drying the soda-lime glass with a mass fraction of calcium oxide of 10% with acetone, anhydrous ethanol and deionized water in sequence;

[0066] Step 2: installing a titanium target material to the cathode target position 1, and then depositing a titanium thin film layer on the soda-lime glass by DC magnetron sputtering in an argon atmosphere to obtain a thin film on the soda-lime glass, wherein the purity of the titanium target material is 5N;

[0067] The distance between the titanium target and the center of the soda-lime glass is 8 cm, and the target sputtering power density is 3.1 W / cm 2 , the target sputtering pressure is 0.4 Pa, and the sputtering time is 1200 s.

[0068] Among them, the total thickness of the titanium film is 150nm.

[0069] Comparative Example 2

[0070] The method is basically the same as Example 1, except that in step 2, a molybdenum target material of the same purity is used instead of a copper target material for DC magnetron sputtering, and the sputtering time is 100 s to obtain a molybdenum thin film layer on the soda-lime glass;

[0071] The thickness ratio of the molybdenum thin film layer to the titanium thin film layer is 1:2.

[0072] Comparative Example 3

[0073] The method is basically the same as Example 1, except that, in step 2, a chromium target material of the same purity is used instead of a copper target material for DC magnetron sputtering, and the sputtering time is 100 s to obtain a chromium thin film layer on the soda-lime glass;

[0074] The thickness ratio of the chromium thin film layer to the titanium thin film layer is 1:2.

[0075] Performance Test:

[0076] Resistance: The thin film characterization resistance is tested using a handheld four-probe square resistance tester. Four probes are equidistantly distributed on the surface of the sample being tested, two of which provide test current and the other two measure voltage. This design can eliminate the influence of wire resistance, probe resistance, and contact resistance between the probe and the material, thereby improving measurement accuracy. Specifically, the two outer probes (probes 1 and 4) provide test current, and the two inner probes (probes 2 and 3) measure voltage. The resistance value of the sample is calculated using Ohm's law to obtain the resistance value.

[0077] After testing, the thin film resistors obtained in the embodiment and the comparative example are shown in Table 1:

[0078] Table 1

[0079] Group Resistance (Ω) Group Resistance (Ω) Example 1 1.0 Example 6 2.9 Example 2 2.2 Example 7 1.8 Example 3 2.1 Comparative Example 1 139.4 Example 4 1.3 Comparative Example 2 25.7 Example 5 8.6 Comparative Example 3 70.5

[0080] Conclusion analysis:

[0081] 1. It can be seen from Examples 1-3 that when the process parameters in the target sputtering process, such as the distance between the target and the center of the substrate, the sputtering power density, etc., are changed, the resistance of the obtained film will also increase to a certain extent. This shows that the process conditions of Example 1 are the best.

[0082] 2. It can be seen from Example 1 and Examples 4-5 that when the total thickness of the thin film layer is the same, when the thickness ratio between the metal thin film layer and the titanium thin film layer in the thin film layer is adjusted, as the thickness of the metal thin film layer changes, the resistance of the thin film composed of the titanium thin film layer will also become higher. This is because when the metal thin film layer becomes thinner, the conductivity of the metal thin film layer will become weaker, thereby causing the resistance of the thin film layer formed by itself and the titanium thin film layer to increase; when the metal thin film layer becomes thicker, it can be seen from Example 4 that the resistance of the film is also relatively low, but as the metal thin film layer in the thin film layer becomes thicker, the titanium thin film will become thinner, thereby affecting the function of the titanium thin film layer. It can be seen that the thickness ratio between the metal thin film layer and the titanium thin film layer in Example 1 is the optimal thickness ratio.

[0083] 3. It can be seen from Examples 1 and 6-7 that when the copper thin film layer is replaced by a nickel thin film layer and an aluminum thin film layer, although the resistance of the obtained thin film is higher than that of Example 1, its resistance is still relatively low. Therefore, it can be seen that the thin film resistances formed by the copper thin film layer, the nickel thin film layer, and the aluminum thin film layer respectively combined with the titanium thin film layer are relatively close.

[0084] 4. It can be seen from Example 1 and Comparative Example 1 that when there is only a titanium thin film layer, the resistance of the film can reach 139.4Ω, but after being combined with a copper thin film layer, the resistance of the film is only 1.0Ω, which is 138.4Ω lower than that of Comparative Example 1;

[0085] Further observing Examples 2-3, when the nickel thin film layer and the aluminum thin film layer were respectively combined with the titanium thin film layer, the resistance of the obtained thin films decreased by 136.5Ω and 137.6Ω respectively relative to the titanium thin film layer of Comparative Example 1;

[0086] It can be seen that the resistance of the thin film layer can be effectively reduced after the titanium thin film layer is combined with the metal thin film layer.

[0087] 5. Comparative Examples 2-3 show that when a molybdenum thin film layer, a chromium thin film layer and a titanium thin film layer are combined, although the resistance of the thin film can be reduced, the effect of the reduction is far less than that of the copper thin film layer;

[0088] When further observing Example 6 and Comparative Example 2, compared with the molybdenum thin film layer formed by the molybdenum metal with better conductivity, the nickel thin film layer formed by the nickel metal with poor conductivity and the titanium thin film layer have lower resistance. It can be seen that not all thin film layers formed by metals with good conductivity can achieve the effects of copper thin film layers, nickel thin film layers, and aluminum thin film layers.

[0089] The above embodiments are preferred implementation modes of the present application, but the implementation modes of the present application are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present application shall be equivalent replacement methods and shall be included in the protection scope of the present application.

Claims

1. A film, characterized in that: The film is composed of a metal film layer and a titanium film layer deposited on the metal film layer; The metal film layer is a copper film layer, a nickel film layer or an aluminum film layer.

2. The film according to claim 1, characterized in that The thickness of the film is 100-200 nm, and the thickness ratio of the metal film layer to the titanium film layer in the film is 1:1-1:

3.

3. The film according to claim 1, characterized in that The metal film layer is obtained by direct current magnetron sputtering of a metal target, wherein the metal target is a copper target, a nickel target or an aluminum target; The titanium thin film layer is obtained by direct current magnetron sputtering of a titanium target.

4. The film according to claim 3, characterized in that The purity of the copper target material, nickel target material, aluminum target material and titanium target material is not less than 5N.

5. A method for preparing a thin film according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: Cleaning the substrate; Step 2: Mount the metal target material on the cathode position No. 1 target for DC magnetron sputtering to deposit the metal film layer on the substrate to obtain the metal film layer on the substrate; Step 3: Install the titanium target on the cathode position No. 2 target and perform DC magnetron sputtering to deposit the titanium thin film layer on the metal thin film layer to obtain a thin film.

6. The preparation method according to claim 5, characterized in that: The substrate is soda-lime glass or silicate glass with a mass fraction of calcium oxide not exceeding 12.5%; The cleaning operation of the substrate is specifically: cleaning and drying by using acetone, anhydrous ethanol and deionized water in sequence.

7. The preparation method according to claim 5, characterized in that: The distance between the metal target and the center of the substrate in step 2 is 6 to 10 cm, and the target sputtering power density is 1.0 to 10.5 W / cm 2 , the target sputtering pressure is 0.2~0.6Pa, and the sputtering time is 40~200s; The distance between the titanium target and the center of the substrate in step 3 is 6 to 10 cm, and the target sputtering power density is 1.0 to 5.2 W / cm 2 , the target sputtering pressure is 0.2~0.6Pa, and the sputtering time is 450~1200s.

8. Use of the film according to any one of claims 1 to 4 in preparing foam iron, LCD displays or thin-film solar cells.

Citation Information

Patent Citations

  • Laminated film and preparation method thereof

    CN118726910A

  • Flexible piezoelectric ultrasonic transducer

    CN113182157A

  • Electrode for living body

    JP1994189919A

  • N-type gallium nitride compound semiconductor electrode and formation thereof

    JP1998084135A

  • Vibrating membrane for electrostatic electroacoustic transducer

    JP2003023698A